Manajemen Hubungan Sekolah dengan Masyarakat di Madrasah Aliyah (MA) Negeri 1 Bone - Rahmawati; Saril (JURNAL MAPPESONA, 2025)
Public relations with schools or better known as public relations have a very important role in an educational institution or school. Its existence has become a trend in the management world in Indonesia, marked by the existence of a public relations division in both for-profit and non-profit companies. Likewise in the world of education known as school administration. Its existence is very important because as a service that can be a liaison between schools and the community in serving administrative needs. In this study, it is revealed how important the management of school relations with the community is in school administration at Ma Al Nur Patangnga, Tellusiating'e District, which starts from the management of public relations in schools. focuses on how important public relations is in improving school administration.